Revegetation in Japan overlooks geographical genetic structure of native Artemisia indica var. maximowiczii populations. Issue 7 (29th October 2021) - Wagatsuma, Satoshi; Imanishi, Junichi; Suyama, Yoshihisa; Matsuo, Ayumi; Sato, Mitsuhiko P.; Mitsuyuki, Chika; Tsunamoto, Yoshihiro; Tominaga, Tohru; Shimono, Yoshiko
Abstract : Although revegetation activities are often accompanied by extensive release of translocated or cultivated individuals into natural communities, their potential effects on native populations are relatively unclear. Understanding the original genetic structures in natural habitats and how the patterns have been maintained in populations at revegetation sites is a critical first step in assessing current revegetation efforts. Artemisia indica var. maximowiczii is a native species commonly used for revegetation in Japan. We assessed the genetic and morphological variations in individuals collected from natural habitats and revegetation sites across Japan, as well as individuals have grown from two types of commercial seeds from China used for revegetation: imported seeds that originated from Chinese populations and reimported seeds that originated from Japanese populations but were cultivated in China. Genome‐wide single nucleotide polymorphism (SNP) data revealed that individuals collected from natural habitats were genetically differentiated between northeastern and southwestern regions in Japan. Individuals grown from the reimported seeds were genetically similar to the northeastern populations in Japan, suggesting their original sources were areas in the northeast. Most individuals collected from revegetation sites were genetically similar to individuals from the reimported seeds, even though the revegetation sites were in southwestern Japan, suggesting that seeds derived from the northeastern populations were used for revegetation throughout Japan. Individuals grown from the imported seeds that originated from China were genetically and morphologically differentiated from native individuals in Japan. Careful consideration should be given to the extensive use of non‐local seeds for revegetation that is sourced only from northeastern Japan or foreign countries.